Rainfall regimes of the Green Sahara - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter B. (Science Advances, 2017)
We estimate rainfall during the “Green Sahara” period. , During the “Green Sahara” period (11,000 to 5000 years before the present), the Sahara desert received high amounts of rainfall, supporting diverse vegetation, permanent lakes, and human populations. Our knowledge of rainfall rates and the spatiotemporal extent of wet conditions has suffered from a lack of continuous sedimentary records. We present a quantitative reconstruction of western Saharan precipitation derived from leaf wax isotopes in marine sediments. Our data indicate that the Green Sahara extended to 31°N and likely ended abruptly. We find evidence for a prolonged “pause” in Green Sahara conditions 8000 years ago, coincident with a temporary abandonment of occupational sites by Neolithic humans. The rainfall rates inferred from our data are best explained by strong vegetation and dust feedbacks; without these mechanisms, climate models systematically fail to reproduce the Green Sahara. This study suggests that accurate simulations of future climate change in the Sahara and Sahel will require improvements in our ability to simulate vegetation and dust feedbacks.

Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation - Muschitiello, Francesco; Pausata, Francesco S. R.; Lea, James M.; Mair, Douglas W. F.; Wohlfarth, Barbara (Nature Communications, 2017)
Abstract Volcanic eruptions can impact the mass balance of ice sheets through changes in climate and the radiative properties of the ice. Yet, empirical evidence highlighting the sensitivity of ancient ice sheets to volcanism is scarce. Here we present an exceptionally well-dated annual glacial varve chronology recording the melting history of the Fennoscandian Ice Sheet at the end of the last deglaciation (∼13,200–12,000 years ago). Our data indicate that abrupt ice melting events coincide with volcanogenic aerosol emissions recorded in Greenland ice cores. We suggest that enhanced ice sheet runoff is primarily associated with albedo effects due to deposition of ash sourced from high-latitude volcanic eruptions. Climate and snowpack mass-balance simulations show evidence for enhanced ice sheet runoff under volcanically forced conditions despite atmospheric cooling. The sensitivity of past ice sheets to volcanic ashfall highlights the need for an accurate coupling between atmosphere and ice sheet components in climate models.

Understanding the Mechanisms behind the Northward Extension of the West African Monsoon during the Mid-Holocene - Gaetani, Marco; Messori, Gabriele; Zhang, Qiong; Flamant, Cyrille; Pausata, Francesco S. R. (Journal of Climate, 2017)
Abstract Understanding the West African monsoon (WAM) dynamics in the mid-Holocene (MH) is a crucial issue in climate modeling, because numerical models typically fail to reproduce the extensive precipitation suggested by proxy evidence. This discrepancy may be largely due to the assumption of both unrealistic land surface cover and atmospheric aerosol concentration. In this study, the MH environment is simulated in numerical experiments by imposing extensive vegetation over the Sahara and the consequent reduction in airborne dust concentration. A dramatic increase in precipitation is simulated across the whole of West Africa, up to the Mediterranean coast. This precipitation response is in better agreement with proxy data, in comparison with the case in which only changes in orbital forcing are considered. Results show a substantial modification of the monsoonal circulation, characterized by an intensification of large-scale deep convection through the entire Sahara, and a weakening and northward shift (~6.5°) of the African easterly jet. The greening of the Sahara also leads to a substantial reduction in the African easterly wave activity and associated precipitation. The reorganization of the regional atmospheric circulation is driven by the vegetation effect on radiative forcing and associated heat fluxes, with the reduction in dust concentration to enhance this response. The results for the WAM in the MH present important implications for understanding future climate scenarios in the region and in teleconnected areas, in the context of projected wetter conditions in West Africa.

The role of the meridional sea surface temperature gradient in controlling the Caribbean low‐level jet - Maldonado, Tito; Rutgersson, Anna; Caballero, Rodrigo; Pausata, Francesco S. R.; Alfaro, Eric; Amador, Jorge (Journal of Geophysical Research: Atmospheres, 2017)
Abstract The Caribbean low‐level jet (CLLJ) is an important modulator of regional climate, especially precipitation, in the Caribbean and Central America. Previous work has inferred, due to their semiannual cycle, an association between CLLJ strength and meridional sea surface temperature (SST) gradients in the Caribbean Sea, suggesting that the SST gradients may control the intensity and vertical shear of the CLLJ. In addition, both the horizontal and vertical structure of the jet have been related to topographic effects via interaction with the mountains in Northern South America (NSA), including funneling effects and changes in the meridional geopotential gradient. Here we test these hypotheses, using an atmospheric general circulation model to perform a set of sensitivity experiments to examine the impact of both SST gradients and topography on the CLLJ. In one sensitivity experiment, we remove the meridional SST gradient over the Caribbean Sea and in the other, we flatten the mountains over NSA. Our results show that the SST gradient and topography have little or no impact on the jet intensity, vertical, and horizontal wind shears, contrary to previous works. However, our findings do not discount a possible one‐way coupling between the SST and the wind over the Caribbean Sea through friction force. We also examined an alternative approach based on barotropic instability to understand the CLLJ intensity, vertical, and horizontal wind shears. Our results show that the current hypothesis about the CLLJ must be reviewed in order to fully understand the atmospheric dynamics governing the Caribbean region. , Key Points Atmospheric dynamics in the Caribbean SST over the Caribbean Sea is examined as kinetic energy source for the CLLJ Impact of meridional SST gradient on the vertical structure of CLLJ

Greening of the Sahara suppressed ENSO activity during the mid-Holocene - Pausata, Francesco S. R.; Zhang, Qiong; Muschitiello, Francesco; Lu, Zhengyao; Chafik, Léon; Niedermeyer, Eva M.; Stager, J. Curt; Cobb, Kim M.; Liu, Zhengyu (Nature Communications, 2017)
Abstract The evolution of the El Niño-Southern Oscillation (ENSO) during the Holocene remains uncertain. In particular, a host of new paleoclimate records suggest that ENSO internal variability or other external forcings may have dwarfed the fairly modest ENSO response to precessional insolation changes simulated in climate models. Here, using fully coupled ocean-atmosphere model simulations, we show that accounting for a vegetated and less dusty Sahara during the mid-Holocene relative to preindustrial climate can reduce ENSO variability by 25%, more than twice the decrease obtained using orbital forcing alone. We identify changes in tropical Atlantic mean state and variability caused by the momentous strengthening of the West Africa Monsoon (WAM) as critical factors in amplifying ENSO’s response to insolation forcing through changes in the Walker circulation. Our results thus suggest that potential changes in the WAM due to anthropogenic warming may influence ENSO variability in the future as well.

On the links between meteorological variables, aerosols, and tropical cyclone frequency in individual ocean basins - Chiacchio, Marc; Pausata, Francesco S. R.; Messori, Gabriele; Hannachi, Abdel; Chin, Mian; Önskog, Thomas; Ekman, Annica M. L.; Barrie, Leonard (Journal of Geophysical Research: Atmospheres, 2017)
Abstract A generalized linear model based on Poisson regression has been used to assess the impact of environmental variables modulating tropical cyclone frequency in six main cyclone development areas: the East Pacific, West Pacific, North Atlantic, North Indian, South Indian, and South Pacific. The analysis covers the period 1980–2009 and focuses on widely used meteorological parameters including wind shear, sea surface temperature, and relative humidity from different reanalyses as well as aerosol optical depth for different compounds simulated by the Goddard Chemistry Aerosol Radiation and Transport model. Circulation indices are also included. Cyclone frequency is obtained from the International Best Track Archive for Climate Stewardship. A strong link is found between cyclone frequency and the relative sea surface temperature, Atlantic Meridional Mode, and wind shear with significant explained log likelihoods in the North Atlantic of 37%, 27%, and 28%, respectively. A significant impact of black carbon and organic aerosols on cyclone frequency is found over the North Indian Ocean, with explained log likelihoods of 27%. A weaker but still significant impact is found for observed dust aerosols in the North Atlantic with an explained log likelihood of 11%. Changes in lower stratospheric temperatures explain 28% of the log likelihood in the North Atlantic. Lower stratospheric temperatures from a subset of Coupled Model Intercomparison Project Phase 5 models properly simulate the warming and subsequent cooling of the lower stratosphere that follows a volcanic eruption but underestimates the cooling by about 0.5°C. , Key Points Significant impact of black carbon and organic aerosols Significant impact of observed dust aerosols in the North Atlantic Lower stratospheric temperatures explain 28% of the log likelihood

Tropical cyclone activity enhanced by Sahara greening and reduced dust emissions during the African Humid Period - Pausata, Francesco S. R.; Emanuel, Kerry A.; Chiacchio, Marc; Diro, Gulilat T.; Zhang, Qiong; Sushama, Laxmi; Stager, J. Curt; Donnelly, Jeffrey P. (Proceedings of the National Academy of Sciences, 2017)
Significance Our modeling study shows the crucial role of vegetation cover over the Sahara and reduced dust emission in altering tropical cyclone activity during the mid-Holocene (6,000 yBP). Our results also demonstrate how these regional changes in land cover and dust emission are able to affect areas far afield through changes of large-scale atmospheric circulation. Our study strongly suggests that an appropriate representation of land cover and dust emission is of paramount importance to be able to capture past—and potentially future—climate changes. , Tropical cyclones (TCs) can have devastating socioeconomic impacts. Understanding the nature and causes of their variability is of paramount importance for society. However, historical records of TCs are too short to fully characterize such changes and paleo-sediment archives of Holocene TC activity are temporally and geographically sparse. Thus, it is of interest to apply physical modeling to understanding TC variability under different climate conditions. Here we investigate global TC activity during a warm climate state (mid-Holocene, 6,000 yBP) characterized by increased boreal summer insolation, a vegetated Sahara, and reduced dust emissions. We analyze a set of sensitivity experiments in which not only solar insolation changes are varied but also vegetation and dust concentrations. Our results show that the greening of the Sahara and reduced dust loadings lead to more favorable conditions for tropical cyclone development compared with the orbital forcing alone. In particular, the strengthening of the West African Monsoon induced by the Sahara greening triggers a change in atmospheric circulation that affects the entire tropics. Furthermore, whereas previous studies suggest lower TC activity despite stronger summer insolation and warmer sea surface temperature in the Northern Hemisphere, accounting for the Sahara greening and reduced dust concentrations leads instead to an increase of TC activity in both hemispheres, particularly over the Caribbean basin and East Coast of North America. Our study highlights the importance of regional changes in land cover and dust concentrations in affecting the potential intensity and genesis of past TCs and suggests that both factors may have appreciable influence on TC activity in a future warmer climate.

Future Response of Temperature and Precipitation to Reduced Aerosol Emissions as Compared with Increased Greenhouse Gas Concentrations - Acosta Navarro, Juan C.; Ekman, Annica M. L.; Pausata, Francesco S. R.; Lewinschal, Anna; Varma, Vidya; Seland, Øyvind; Gauss, Michael; Iversen, Trond; Kirkevåg, Alf; Riipinen, Ilona; Hansson, Hans Christen (Journal of Climate, 2017)
Abstract Experiments with a climate model (NorESM1) were performed to isolate the effects of aerosol particles and greenhouse gases on surface temperature and precipitation in simulations of future climate. The simulations show that by 2025–49 a reduction of aerosol emissions from fossil fuels following a maximum technically feasible reduction (MFR) scenario could lead to a global and Arctic warming of 0.26 and 0.84 K, respectively, as compared with a simulation with fixed aerosol emissions at the level of 2005. If fossil fuel emissions of aerosols follow a current legislation emissions (CLE) scenario, the NorESM1 model simulations yield a nonsignificant change in global and Arctic average surface temperature as compared with aerosol emissions fixed at year 2005. The corresponding greenhouse gas effect following the representative concentration pathway 4.5 (RCP4.5) emission scenario leads to a global and Arctic warming of 0.35 and 0.94 K, respectively. The model yields a marked annual average northward shift in the intertropical convergence zone with decreasing aerosol emissions and subsequent warming of the Northern Hemisphere. The shift is most pronounced in the MFR scenario but also visible in the CLE scenario. The modeled temperature response to a change in greenhouse gas concentrations is relatively symmetric between the hemispheres, and there is no marked shift in the annual average position of the intertropical convergence zone. The strong reduction in aerosol emissions in the MFR scenario also leads to a net southward cross-hemispheric energy transport anomaly both in the atmosphere and ocean, and enhanced monsoon circulation in Southeast Asia and East Asia causing an increase in precipitation over a large part of this region.

The PMIP4 contribution to CMIP6 – Part 2: Two interglacials, scientific objective and experimental design for Holocene and Last Interglacial simulations - Otto-Bliesner, Bette L.; Braconnot, Pascale; Harrison, Sandy P.; Lunt, Daniel J.; Abe-Ouchi, Ayako; Albani, Samuel; Bartlein, Patrick J.; Capron, Emilie; Carlson, Anders E.; Dutton, Andrea; Fischer, Hubertus; Goelzer, Heiko; et al. (Geoscientific Model Development, 2017)
Abstract. Two interglacial epochs are included in the suite of Paleoclimate Modeling Intercomparison Project (PMIP4) simulations in the Coupled Model Intercomparison Project (CMIP6). The experimental protocols for simulations of the mid-Holocene (midHolocene, 6000 years before present) and the Last Interglacial (lig127k, 127 000 years before present) are described here. These equilibrium simulations are designed to examine the impact of changes in orbital forcing at times when atmospheric greenhouse gas levels were similar to those of the preindustrial period and the continental configurations were almost identical to modern ones. These simulations test our understanding of the interplay between radiative forcing and atmospheric circulation, and the connections among large-scale and regional climate changes giving rise to phenomena such as land–sea contrast and high-latitude amplification in temperature changes, and responses of the monsoons, as compared to today. They also provide an opportunity, through carefully designed additional sensitivity experiments, to quantify the strength of atmosphere, ocean, cryosphere, and land-surface feedbacks. Sensitivity experiments are proposed to investigate the role of freshwater forcing in triggering abrupt climate changes within interglacial epochs. These feedback experiments naturally lead to a focus on climate evolution during interglacial periods, which will be examined through transient experiments. Analyses of the sensitivity simulations will also focus on interactions between extratropical and tropical circulation, and the relationship between changes in mean climate state and climate variability on annual to multi-decadal timescales. The comparative abundance of paleoenvironmental data and of quantitative climate reconstructions for the Holocene and Last Interglacial make these two epochs ideal candidates for systematic evaluation of model performance, and such comparisons will shed new light on the importance of external feedbacks (e.g., vegetation, dust) and the ability of state-of-the-art models to simulate climate changes realistically.